Pemberdayaan Masyarakat Untuk Tata Kelola Kelembagaan dan Usaha Aren Pada Hutan Kemasyarakatan di Aik Bual Lombok Tengah - Markum; Andy C. Ichsan; Dwi Sukma Rini; Maiser Saputra (Fakultas Pertanian Universitas Mataram, 2020)
Three main problems still faced by sugar palm farmers in Aik Bual Village, namely the crop cultivation system has not been well planned; Social Forestry Business Group institutions are not yet independent; and product performance is not yet competitive. The objectives of community service activities are: a) to facilitate KUPS in implementing better palm cultivation; b). improve the skills of KUPS administrators in implementing independent institutional governance, and c) facilitate the production of more varied and quality palm processed products. The activity approach uses an active participation method, which involves farmers, KUPS administrators and producers of processed palm products who are beneficiaries, in the process of activities, involving 25 participants. The material presented in the service includes a). Sustainable forest management based on Social Forestry; b). building an independent and developing KUPS institution; c). developing a variety of sap processed products and market opportunities; and D). conservation techniques in community forest-based palm habitat management. The results of the dedication show that a). Sugar plant cultivation system is carried out through natural growth from tillers, growth is quite good, and to optimize the cultivation of sugar is directed to plant propagation by taking into account the availability of nutrients and sufficient sunlight, as well as 6 m spacing. b). so that groups are more independent, especially in developing businesses, encouraged the need to develop cooperation by creating trust through contract agreements, and carrying out product promotions through low-cost social media; c). In order to increase sales volume and make product competition more competitive, it is necessary to carry out a strategy to increase packaging performance and reduce selling prices.